Effective intercalation of zein into Na-montmorillonite: role of the protein components and use of the developed biointerfaces - Alcântara, Ana C. S.; Darder, Margarita; Aranda, Pilar; Ruiz-Hitzky, Eduardo (Beilstein Journal of Nanotechnology, 2016)
Biohybrid materials based on the intercalation of zein, the major storage protein in corn, into sodium-exchanged montmorillonite were prepared following two synthesis strategies. The first one made use of zein dissolved in 80% (v/v) ethanol/water solution, the usual solvent for this protein, while the second method is new and uses a sequential process that implies the previous separation of zein components in absolute ethanol. This treatment of zein with ethanol renders a soluble yellow phase and an agglomerate of insoluble components, which are able to intercalate the layered silicate when an aqueous dispersion of montmorillonite is added to the ethanol medium containing both phases. The diverse steps in this second route were investigated individually in order to understand the underlying mechanism that drives to the intercalation of this complex hydrophobic biomacromolecule into the hydrophilic interlayer space of sodium-exchanged montmorillonite. In addition to physicochemical characterization of the resulting materials, these biohybrid interfaces were also evaluated as biofillers in the preparation of diverse ecofriendly nanocomposites.
Keywords: biohybrids; biointerfaces; bionanocomposites; montmorillonite; zein

(untitled) - Sanchez, C.; Belleville, P.; Popall, M.; Nicole, L. (Chem. Soc. Rev., 2011)

Bio-inorganic Hybrid Nanomaterials - Strategies, Syntheses, Characterization and Application - Ruiz-Hitzky, E.; Darder, M.; Aranda, P. (An introduction to bio-nanohybrid materials, 2008)

Handbook of Clay Science - Brigatti, M. F.; Galán, E.; Theng, B. K. G. (Structures and mineralogy of clay minerals, 2006)

(untitled) - Talibudeen, O. (Nature, 1950)

(untitled) - De Cristofaro, A.; Violante, A. (Appl. Clay Sci., 2001)

(untitled) - Darder, M.; Ruiz, A. I.; Aranda, P.; Van Damme, H.; Ruiz-Hitzky, E. (Curr. Nanosci., 2006)

(untitled) - Chen, P.; Zhang, L. (Biomacromolecules, 2006)

(untitled) - Lin, J.-J.; Wei, J.-C.; Juang, T.-Y.; Tsai, W.-C. (Langmuir, 2007)

(untitled) - Fernandes, F. M.; Ruiz, A. I.; Darder, M.; Aranda, P.; Ruiz-Hitzky, E. (J. Nanosci. Nanotechnol., 2009)

(untitled) - Tran, A. T. T.; James, B. J. (Colloids Surf., A, 2012)

Organic Geochemistry - Weiss, A. (Springer Verlag, 1969)

(untitled) - Chao, V. W.-K.; Hsu, C.-C.; Lu, W.-M.; Chen, W.-J.; Naveen, B.; Tsai, T.-Y. (RSC Adv., 2015)

(untitled) - Bicudo, R. C.; Bicudo, T. C.; Forato, L. A.; Colnago, L. A.; Lanças, F. M. (Comun. Tec. - EMBRAPA, Cent. Pesqui. Agropecu. Trop. Umido, 2006)

(untitled) - Lawton, J. W. (Cereal Chem., 2002)

(untitled) - Anderson, T. J.; Lamsal, B. P. (Cereal Chem., 2011)

(untitled) - Shukla, R.; Cheryan, M. (Ind. Crops Prod., 2001)

(untitled) - Paliwal, R.; Palakurthi, S. (J. Controlled Release, 2014)

(untitled) - Li, Y.; Li, J.; Xia, Q.; Zhang, B.; Wang, Q.; Huang, Q. (J. Phys. Chem. B, 2012)

(untitled) - Sun, C.; Dai, L.; He, X.; Liu, F.; Yuan, F.; Gao, Y. (Food Hydrocolloids, 2016)

(untitled) - Luecha, J.; Sozer, N.; Kokini, J. L. (J. Mater. Sci., 2010)

(untitled) - Nedi, I.; Maio, E. D.; Iannace, S. (J. Appl. Polym. Sci., 2012)

Proceedings of the ACS Division of Polymeric Materials: Science & Engineering - Alcântara, A. C. S.; Aranda, P.; Darder, M.; Ruiz-Hitzky, E. (241st National Meeting and Exposition of the American-Chemical-Society (ACS), Anaheim, CA, 27.3.2011-31.3.2011)

(untitled) - Wicklein, B.; Darder, M.; Aranda, P.; Ruiz-Hitzky, E. (Langmuir, 2010)

(untitled) - Yang, L.; Phua, S. L.; Teo, J. K. H.; Toh, C. L.; Lau, S. K.; Ma, J.; Lu, X. (ACS Appl. Mater. Interfaces, 2011)

(untitled) - Alcântara, A. C. S.; Darder, M.; Aranda, P.; Ruiz-Hitzky, E. (Eur. J. Inorg. Chem., 2012)

(untitled) - Phua, S. L.; Yang, L.; Toh, C. L.; Huang, S.; Tsakadze, Z.; Lau, S. K.; Mai, Y.-W.; Lu, X. (ACS Appl. Mater. Interfaces, 2012)

(untitled) - Chivrac, F.; Pollet, E.; Dole, P.; Avérous, L. (Carbohydr. Polym., 2010)

(untitled) - Alcântara, A. C. S.; Darder, M.; Aranda, P.; Ayral, A.; Ruiz-Hitzky, E. (J. Appl. Polym. Sci., 2016)

(untitled) - Cabra, V.; Arreguin, R.; Galvez, A.; Quirasco, M.; Vazques-Duhalt, R.; Farres, A. (J. Agric. Food Chem., 2005)

(untitled) - Esen, A. (J. Cereal Sci., 1987)

(untitled) - Sessa, D. J.; Eller, F. J.; Palmquist, D. E.; Lawton, J. W. (Ind. Crops Prod., 2003)

(untitled) - Momany, F. A.; Sessa, D. J.; Lawton, J. W.; Selling, G. W.; Hamaker, S. A.; Willett, J. L. (J. Agric. Food Chem., 2006)

(untitled) - Forato, L. A.; Bicudo, T. C.; Colnago, L. A. (Biopolymers, 2003)

(untitled) - Theng, B. K. G.; Newman, R. H.; Whitton, J. S. (Clay Miner., 1998)

(untitled) - Wang, Q.; Crofts, A. R.; Padua, G. W. (J. Agric. Food Chem., 2003)

(untitled) - Park, J. H.; Park, S. M.; Kim, Y. H.; Oh, W.; Lee, G. W.; Karim, M. R.; Park, J. H.; Yeum, J. H. (J. Compos. Mater., 2012)

(untitled) - Ozcalik, O.; Tihminlioglu, F. (J. Food Eng., 2013)

Handbook of Layered Materials - Ruiz-Hitzky, E.; Aranda, P.; Serratosa, J. M. (Clay-organic interactions: Organoclay complexes and polymer-clay nanocomposites, 2004)

(untitled) - Alexandre, M.; Dubois, P. (Mater. Sci. Eng., R, 2000)